S100A9 Tetramers, Which are Ligands of CD85j, Increase the Ability of MVA(HIV)-Primed NK Cells to Control HIV Infection - Moreno-Nieves, Uriel Y. (Front Immunol, 2015)
Natural killer (NK) cells are the major antiviral effector population of the innate immune system. We previously found that S100A9 is a novel ligand of the receptor CD85j and that S100A9 tetramers enhance the anti-HIV activity of NK cells. Also, we found that dendritic cells (DCs) infected by the HIV vaccine candidate, MVA(HIV), prime NK cells to specifically control HIV infection in autologous CD4(+) T cells. In this study, we analyzed whether stimulation of NK cells by S100A9 tetramers prior to the priming by MVA(HIV)-infected DCs modulates the subsequent anti-HIV activity of NK cells. We found that S100A9 tetramers activate NK cells and that DCs enhance the anti-HIV activity of NK cells. Interestingly, we observed that stimulation of NK cells by S100A9 tetramers, prior to the priming, significantly increased the subsequent anti-HIV activity of NK cells and that the enhanced anti-HIV activity was observed following different conditions of priming, including the MVA(HIV)-priming. As S100A9 tetramers alone directly increase the anti-HIV activity of NK cells and as this increased anti-HIV activity is also observed following the interaction of NK cells with MVA(HIV)-infected DCs, we propose S100A9 tetramers as potential adjuvants to stimulate the anti-HIV activity of NK cells.